2016
DOI: 10.4238/gmr.15039003
|View full text |Cite
|
Sign up to set email alerts
|

JNK pathway and relative transcriptional factor were involved in ginsenoside Rh2-mediated G1 growth arrest and apoptosis in human lung adenocarcinoma A549 cells

Abstract: ABSTRACT. Ginsenoside Rh2 has been shown to have an antitumor effect on a wide range of cancers. A previous study has shown that ginsenoside Rh2 can inhibit the proliferation of the human lung adenocarcinoma A549 cell line in a dose-dependent manner by activating caspase-8/3 activity to promote apoptosis. However, the association of the JNK signaling pathways and transcription factors with ginsenoside Rh2 in the suppression of non-small cell lung cancer has not yet been reported. In this study, we found that g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…The results revealed that GRh2 impaired HeLa cell proliferation in a doseand time-dependent manner. These findings are in accordance with previous reports that demonstrated that ginseng Rh2 prevents cell proliferation in colon, lung, liver, and gastric cancers, in addition to leukemia and glioblastoma (38)(39)(40)(41)(42). In addition, it was observed that GRh2 inhibited the activation of the Akt pathway in HeLa cells.…”
Section: Discussionsupporting
confidence: 93%
“…The results revealed that GRh2 impaired HeLa cell proliferation in a doseand time-dependent manner. These findings are in accordance with previous reports that demonstrated that ginseng Rh2 prevents cell proliferation in colon, lung, liver, and gastric cancers, in addition to leukemia and glioblastoma (38)(39)(40)(41)(42). In addition, it was observed that GRh2 inhibited the activation of the Akt pathway in HeLa cells.…”
Section: Discussionsupporting
confidence: 93%
“…The results demonstrated that G-Rh2 decreased the expression of Bcl-2 and increased the expression of Bax, caspase-3 and Smad4 in LoVo/L-OHP and LoVo cells. As reported previously, G-Rh2 inhibits tumor cell growth and prevents cells from entering the growth phase, including the G2/M, G1/S and S phases, respectively (25,26). G-Rh2 can inhibit A172 human glioma cell proliferation and induce cell cycle arrest status (27).…”
Section: Discussionsupporting
confidence: 61%
“…A previous study reported that G-Rh2 induces apoptosis via the activation of caspase-1 and −3 and upregulation of Bax in human neuroblastoma (17). G-Rh2 can inhibit the proliferation of the A549 human lung adenocarcinoma cell line in a dose-dependent manner by activating caspase-8/3 to promote apoptosis (25). In the present study, the effects of G-Rh2 on cell apoptosis-related molecules were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the MAP kinase cascade such as JNK and p38 could be activated by PAKs 1-3 in related study [26]. Moreover, JNK and p38 signaling pathway are considered as critical signal transduction pathways involved in cell proliferation, cell cycle arrest, and apoptosis [27]. Besides, PAK has been shown to protect apoptotic signals by promoting translocation of Raf-1 to the mitochondria, triggering formation of Raf-1-Bcl-2 complexes, and depressing the formation of BAD-Bcl-2 complexes [28].…”
Section: Discussionmentioning
confidence: 93%